Thailand's ICT Readiness for the ASEAN Economic Community. Issue 1 (5th December 2017) - Wongwuttiwat, Jittima
Abstract: ICT development in Thailand and the other ASEAN members must be prepared for the environment of the ASEAN Economic Community (AEC) which will start formally at the end of the year 2015. The Ministry of ICT in Thailand has established several ICT policies and programs for ICT administrative management in both public and private enterprises in order to create a strong network of relationships to deal with competitors in ASEAN. This study compares Thailand with the other ASEAN Plus 3 member nations based on their stage of economic development and three important indicators of competitiveness (the higher education system, technology readiness, and business innovation). The findings identify Thailand's position with respect to ICT development relative to the other ASEAN Plus 3 nations and point to strategies and partnerships that need to be developed in Thailand in order to maintain a competitive position within the AEC.